2012
DOI: 10.1080/19361521.2012.671794
|View full text |Cite
|
Sign up to set email alerts
|

Victimization History and Posttraumatic Stress: An Analysis of Psychopathy Variants in Male Juvenile Offenders

Abstract: Theory and empirical research suggest that psychopathy may be disaggregated into primary and secondary variants. In practice, individuals with high scores on psychopathy measures are treated as a homogenous group. In this study, interviewers recruited 355 incarcerated youth to assess potential differences in trauma history, posttraumatic stress disorder (PTSD) symptoms, and dissociative symptoms among high-anxious (secondary) and low-anxious (primary) variants of psychopathy. Results indicate that youth with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
75
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 38 publications
17
75
0
1
Order By: Relevance
“…secondary psychopathy). Consistent with their proposed greater exposure to negative life events, Tatar, Cauffman, Kimonis, and Skeem (2012) found that incarcerated boys classified in the secondary psychopathy group manifested greater past symptoms of PTSD than their primary psychopathy counterparts.…”
Section: Introductionsupporting
confidence: 59%
“…secondary psychopathy). Consistent with their proposed greater exposure to negative life events, Tatar, Cauffman, Kimonis, and Skeem (2012) found that incarcerated boys classified in the secondary psychopathy group manifested greater past symptoms of PTSD than their primary psychopathy counterparts.…”
Section: Introductionsupporting
confidence: 59%
“…Consistent with prior empirical studies of psychopathy variants (Hicks, Markon et al 2004; Skeem, Johansson et al 2007; Hicks, Vaidyanathan et al 2010; Kimonis, Skeem et al in press; Tatar, Cauffman et al in press), we first used model-based cluster analysis (MBC; Banfield and Raftery 1993) to determine whether primary and secondary variants of juvenile psychopathy can be identified in a subsample of male juvenile offenders scoring high on a measure of psychopathy. To validate the resultant clusters we used multivariate analyses of variance (MANOVA) and analyses of variance (ANOVA) to compare them on theoretically relevant factors not used to derive them, namely maltreatment history and psychiatric symptomatology, predicting that secondary variants will show greater levels of each than primary variants.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, much of the past work on variants of CU traits in samples of youths has relied on self-report (Bjørnebekk & Gjesme, 2009; Kimonis et al, 2012; Roose et al, 2011; Tatar et al, 2012; Vaughn et al, 2009). Some of the differences between the two variants in the current study were significant only when self-report measures were used.…”
Section: Discussionmentioning
confidence: 99%